2016
DOI: 10.1126/science.aad2571
|View full text |Cite
|
Sign up to set email alerts
|

The maternal microbiota drives early postnatal innate immune development

Abstract: Postnatal colonization of the body with microbes is assumed to be the main stimulus to postnatal immune development. By transiently colonizing pregnant female mice, we show that the maternal microbiota shapes the immune system of the offspring. Gestational colonization increases intestinal group 3 innate lymphoid cells and F4/80(+)CD11c(+) mononuclear cells in the pups. Maternal colonization reprograms intestinal transcriptional profiles of the offspring, including increased expression of genes encoding epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
765
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 944 publications
(829 citation statements)
references
References 54 publications
22
765
0
11
Order By: Relevance
“…In addition, recent studies have shown that maternal antibodies alter postnatal immunity by increasing aryl hydrocarbon receptors for maternal bacterial metabolites. 144 Additional study is needed into the role of steroidogenesis and gut epithelium function in the developing fetus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have shown that maternal antibodies alter postnatal immunity by increasing aryl hydrocarbon receptors for maternal bacterial metabolites. 144 Additional study is needed into the role of steroidogenesis and gut epithelium function in the developing fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent evidence using GF animals also points to a role for the maternal microbiota in influencing early postnatal innate immune development in the infant. In this study monocolonization of GF animals with Escherichia coli HA107 during pregnancy altered the numbers of early postnatal intestinal innate leukocytes and increased small intestinal innate lymphoid cell (ILC) proportions and total numbers compared with GF controls, particularly the NKp46 + RORγt + ILC3 subset (Gomez de Aguero et al, 2016).…”
Section: Microbes and Immunitymentioning
confidence: 90%
“…Such influences may be effected through factors including microbial molecular transfer mediated by maternal immunoglobulins transmitted both trans-placentally and through lactation. 48 Defining the interrelated processes of human immune development and microbial acquisition may have a significant impact on our understanding of the pathogenesis of IBD.…”
mentioning
confidence: 99%